Effectiveness of Cognitive Restructuring Techniques in Increasing Self-Efficacy for Learning Achievement - Hasan, Zulfiah; Maghfiroh, Nasruliyah Hikmatul; Fauziyah, Nailul (IAIN Kudus, 2024)
Effectiveness of Cognitive Restructuring Techniques in Increasing Self-Efficacy for Learning Achievement. Self-efficacy is an individual's belief in managing abilities and carrying out activities such as completing assignments. A student who has learning difficulties tends to have low self-efficacy in achieving learning achievement. Students should be encouraged to have high self-efficacy. Higher self-efficacy indicates a more persistent attitude, is involved in learning, is not worried, and does not experience pressure in facing problems. This study aims to describe the effect of providing group counseling using cognitive restructuring techniques on student learning achievement. This study is a quasi-experimental study with a one group pre-test-post-test design. The subjects of this study were seven students. The questionnaire used was a self-efficacy questionnaire. Data analysis used paired t-test statistics, previously the research data had been tested for normality using Kolmogorov-Smirnov. The results showed that there were significant changes in students' self-efficacy before and after the intervention.Keywords: Cognitive Restructuring, Self-Efficacy, Learning Achievement